Answer:
Explanation:
Call h(x) = y (It's easier to see).
y = -x - 1
The first step is always to interchange x and y
y = -x - 1
-x = y - 1
Solve for y
-x + 1 = y
If I understand the question, these two (f(x) and h(x)) are not inverses.
10 is a bit tricky. An inverse can invert into itself: This is called an involution. But if they are differently labeled, I'm not sure. I don't think that this is exactly what is men by an involution. Something like y = x would be. But you have 2 different inverses. I'm not sure that this qualifies.
y = x + 3
g = x + 3
x = y + 3
x - 3 = y